Sintesis Penyesuaian Klasik Pavlov dan Periode Kognitif Piaget dalam Prinsip Pembelajaran Komprehensif - Firmansyah, Yoga Adhitya Fredy; Aisyah Karunia Ramadhani; Muhammad Iqbaal Al Ghifari; M. Yunus Abu Bakar (Mathematics Education Study Program, 2025)
This investigation endeavors to explore the integration of Pavlov's classical conditioning theory with Piaget's stages of cognitive development in the articulation of comprehensive learning principles. The methodological approach adopted is a systematic literature review that amalgamates core tenets from Pavlovian theory and Piaget's cognitive developmental phases. The outcomes demonstrate that the confluence of these two paradigms furnishes a robust foundation for devising adaptive learning frameworks oriented toward holistic student maturation. This synthesis emphasizes that comprehensive learning extends beyond mere stimulus-response dynamics, incorporating students' cognitive progression and mental engagements. Accordingly, this framework enables the formulation of dynamic and contextually attuned learning experiences commensurate with students' developmental exigencies. The study asserts that the convergence of classical and cognitive theories is imperative as a cornerstone for contemporary pedagogical practices.